신선 채소류의 부패에 따른 세균의 다양성 변화 및 세균에 의한 채소 부패 조사 - 이동환(Dong Hwan Lee); 유정일(Jungel Ryu); 박소연(So Yeon Park); 노은정(Eunjung Roh); 오창식(Chang-sik Oh); 정규석(Kyu Suk Jung); 윤종철(Jongchul Yoon); 허성기(Sunggi Heu) (Sigmulbyeong yeon'gu, 2011)
Almost 10~30% of vegetables were discarded by the spoilage from farms to tables. After harvest, vegetables are often spoiled by a wide variety of microorganisms including many bacterial and fungal species. This investigation was conducted to extent the knowledge of relationship the spoilage of vegetables and the diversity of microbes. The total aerobic bacterial numbers in fresh lettuce, perilla leaf, and chicory were $2.6{\sim}2.7{×}10^6$, $4.6{×}10^5$, $1.2{×}10^6\;CFU/g$ of fresh weight, respectively. The most common bacterial species were Pseudomonas spp., Alysiella spp., and Burkholderia spp., and other 18 more genera were involved in. After one week of incubation of those vegetables at $28^{°}C$, the microbial diversity had been changed. The total aerobic bacterial numbers increased to $1.1{\sim}4.6{×}10^8$, $4.9{×}10^7$, and $7.6{×}10^8\;CFU/g$ of fresh weight for lettuce, perilla leaf, and chicory that is about $10^2$ times increased bacterial numbers than that before spoilage. However, the diversity of microbes isolated had been simplified and fewer bacterial species had been isolated. The most bacterial population (~48%) was taken up by Pseudomonas spp., and followed by Arthrobacter spp. and Bacillus spp. The spoilage activity of individual bacterial isolates had been tested using axenic lettuce plants. Among tested isolates, Pseudomonas fluorescence and Pantoea agglomerans caused severe spoilage on lettuce. 채소류가 소비되기까지 약 10~30%에 이르는 양이 부패에 의해 버려지고 있다. 채소류는 수확 후 수많은 세균이나 곰팡이와 같은 다양한 미생물들에 의해 부패가 이루어진다. 채소류의 부패와 세균과의 관계를 알아보고자 세균의 다양성에 관한 조사를 하였다. 신선한 상추와 깻잎, 치커리에서의 총 호기성 균 수는 각각 $2.6{\sim}2.7{×}10^6$, $4.6{×}10^5$, $1.2{×}10^6\;CFU/g$ of fresh weight이었으며, Pseudomonas spp., Alysiella spp., Burkholderia spp.와 그 외의 18개의 다양한 속들이 확인되었다. 신선한 채소류를 $28^{°}C$에서 일주일 동안 배양하였을 때 세균 다양성에 변화가 생겼다. 총 호기성 균의 수는 상추와 깻잎, 치커리에 대하여 각각 $1.1{\sim}4.6{×}10^8$, $4.9{×}10^7$, $7.6{×}10^8\;CFU/g$ of fresh weight로 나타났으며, 이는 약 $10^2$배 정도 증가한 수치이다. 하지만 세균 다양성은 단순해져서 보다 적은 수의 세균이 분리, 동정되었다. Pseudomonas spp.가 대부분을 차지하였으며(~48%), Arthrobacter sp., Bacillus sp.가 그 뒤를 이었다. 동정된 세균 각각의 부패능을 검정하고자 무균배양한 상추에 접종하였으며, 그 결과 Pseudomonas fluorescence와 Pantoea agglomerans가 상당한 부패를 야기하였다.